Lavagem de capitais: administração de justiça e ordem socioeconômica como bens jurídicos tutelados - Souto, Arthur Heinstein Apolinário (2013)
This dissertation aims to analyze some points of major importance within the theme money laundering. It is a scientific research, using qualitative and historical methods, because if provides an overview of the historical evolution of this behavior and makes a literature review of books, magazines, periodicals, websites and jurisprudence on the topic. The theme focused on attempts to achieve a criminal reality quite refined, improved and little known, even by most jurists since, amounts to a legislative innovation of considerable complexity. The objective is to expose the density of theme, had its own particularities, summarizing the historical evolution of anti-money laundering legislation, showing generations by passing or may pass such laws, in an attempt to contextualize the topic, presenting the concepts that reach such criminal and the various terms used as synonymous, thus showing that, due to their complexity, some phases sometimes be necessary to show that the capital of illicit origin are being reintroduced to the socio-economic-financial system, to gain the appearance of legitimate . Search will, within this context, presenting the legal interests protected by the standard anti-money laundering, interconnecting it to the criminal aspects of the law 9.613/98, exposing finally some ensure measures to combat and prevent washing. Compared to the plexus of the criminal action that achieves this offense, the call for new and efficient legal systems is worldwide, making a recommendation to the constitution of international legal texts, treaties, conventions etc. enabling all countries act cooperatively to combat money laundering. Worries thus not enhance the legislative tool that is available, but criticize it properly, only in their gaps, because there are many who admonish National Legislation anti-money laundering, however, few collaborate to address their breaches. Faced with increased macro crime organized and the large sums raised by them, upon exercise of their criminal activities, combined with the easy movement of values around the world and use these facilities to hide the values from the crimes committed by criminal bands mentioned, a concern of international order gained intensity in order to curb legally and said concrete globalized phenomenon. The problem evidenced in this work goes beyond the barriers of criminal policy, legal rulings and doctrinal studies on the topic. Its consequences are deleterious and that shows more concern is its scope, the constituency that borders finds no criminal activity. The only way to prevent such crime and to control it with the required property is taking it seriously. Recognizing the magnitude and wishing are truly creating a structure capable of detecting crime prior placate him at home. The Implementation of public policies, the rigging of the competent authorities involved in combating money laundering, awareness of financial institutions, the resurgence of standards etc., Initiatives that are in the medium term could make concrete have some effect, with respect to this crime decreased as offensive to the world society.